USAGE OF CUSTOMER’S MATERIALS FOR CONSTRUCTION - O. S. Golubova (Наука и техника)
A system of interrelations between a customer and a contractor envisages various approaches to supply of construction sites with materials while preparing a construction contract. This commitment may be taken by a contractor or a customer. Taking into account requirements of tax legislation it is possible to make a conclusion that supply of sites with customer’s materials permits to decrease expenses for construction by 13–14 %.